The environmental education from the interdisciplinary practices: Dom Érico Ferrari Elementary State School, Nova Palma/RS - Helena Maria Beling; Janete Webler Cancelier; Michele Hennig Vestena; Josiane Oliveira de Campos (Universidade Estadual de Alagoas, 2021)
Comprehending the role that school education plays in contemporary society, from its practices and pedagogical actions, is extremely important. The projects and educational activities developed inside the school environment, help in the formation of citizens with critical awareness. In this regard, this paper aims to comprehend the value of the environmental education interdisciplinary projects developed by a rural elementary school -Dom Érico Ferrari Elementary State School, located in the town of Nova Palma/RS, covering the "garden at school" and "honey and its uses" projects, elaborated, respectively, with students from the 9th grade and 1st to the 4th grade. The methodology is based on a qualitative approach, held bibliographic, documentary and field research, besides the application of interviews to thepeople involved in the projects. As a result, the presented projects were effective, contemplating the environment education in its practices in different contexts and spaces, including the school and its community. The projects are important because of the socio-environmental debates and the critical ideas implemented in a variety of subjects of the academic curriculum, motivating the knowledge exchange, since it works with questions related to the reality of the students.